(untitled) (Studia Prawnicze / The Legal Studies, 1964)
This article is about selected problems of the construction and installation agreements for works carried out with the aim of implementing plans for the capital construction of socialist organizations. In particular, issues such as the purpose and subject of the agreement, the procedure for concluding an agreement, the nature of general work contract, the nature of preliminary construction agreement, and the main obligations of the parties under a construction direct agreement are considered. This article is based on an analysis of resolutions and orders that have legal force in the Polish People’s Republic. The construction and installation agreements are regulated by resolutions issued by the supreme bodies of the economic administration; these resolutions are considered leges spéciales in relation to general provisions of civil law, especially those included in the Code of Obligations. However, these last resolutions have only an auxiliary value, as they belong to the pre-war period. In 1963, the government submitted a draft Civil Code to the Sejm; it also regulated relations in socialist circulation and contained the main regulations on contracts for capital construction. In this article, the author also takes into account the main provisions adopted in this draft. General characteristics of the development of relations in construction. We can see a general picture of the development of productive forces in construction since ancient times and the impact of this development on production relations and their legal formalization. Only at the stage of the highest development of capitalism in the 19th century, the final separation of the contracting agreement took place, and the bourgeois codes regulated it relying mainly on the relations that prevailed in construction. The process of the construction industrialization leads to the fact that relations in construction are increasingly moving in this century from the plane of contracting agreements to the plane of contracts for the sale or supply of finished construction objects, as a result of which the institution of contracting agreements loses its importance. Meanwhile, it continues to act as an instrument of exploitation of small entrepreneurs and artisans by large construction companies. Wishing to avoid the obligations imposed by labour legislation, capitalist enterprises prefer to clothe the relationship of subordination, the relationship of wage labour in the form of contracting agreements. In the socialist literature, there are still no studies dedicated to the issue of the general laws of socialist construction in the field of capital work and forms of co-operation. The example of the Soviet Union shows that, using the experience of the capitalist construction, especially in such highly industrialized countries as the United States of America, the socialist construction has embarked on its own course of development giving much better and faster effects of expanded reproduction of the fixed assets of the socialist economy. The features of the socialist construction can be characterized as follows: 1) a particularly strong degree of linkage of this construction in all countries of the socialist community with the method of administrative, directive planning and management; 2) a gradual transition from the so-called economic system to a contracting system connected with the establishment of large specialized construction companies; 3) the introduction of the principle of general contract, that is, the transfer of coordination functions to one general contractor; 4) separation of functions for the design of the construction site and its implementation through the appointment of special organizations involved in design; 5) organization of special system of financing and control over investments and legal differentiation of financial resources allocated for investments from other funds of socialist organizations. These general distinctive features are subject to greater or lesser modifications in some socialist countries, depending on a number of specific features and objective conditions prevailing in a particular country. And The purpose of the contract (agreement) and the subject matter of obligations in the construction contracts (agreements). According to Polish civil law, the validity of a contract depends in particular on whether its purpose and content are contrary to law, public order and the principles of social cohabitation. The concept of the purpose of a contract in theory and in court decisions has not received an unambiguous definition. The contracts containing impossible (actually or legally) obligations are also invalid. The author proves that the foundations of a socialist planned economy require that the concept of the purpose of a contract should be given an objective meaning (the purpose is the socio-economic consequences resulting from the contract implementation). A contract for work aimed at making illegal, that is, unscheduled investments, should be considered invalid. If the content of a contract is in conflict with the law or the foundations of cohabitation, then we should admit that the conversion of a partially invalid contract is permissible. If, contrary to the current procedure for accepting orders, the contractor assumes obligations the fulfilment of which would make it impossible to fulfil an order of the authorized organization, then the obligation assumed earlier should be considered as having no effect on the entitled party. The purpose of the construction and installation agreement (contract) is the implementation of the planned target, and the subject of the contractor’s obligation is a certain construction facility. However, the general contractor is responsible not only for the implementation of a particular project but also for the object compliance with the investment task. General contract and subcontract. According to the current Polish regulations, the institution of general contracting is optional; the investor is obliged to enter into a general contract with the relevant construction company only if they are not able to organize and coordinate the work carried out by the so-called partial contractors. If an enterprise undertakes to perform the functions of a general contractor, then it itself enters into contracts with other (specialized) contractors or so-called subcontractors; however, the latter are responsible for the work entrusted to them directly before the customer, that is, before the investor, on an equal footing with a general contractor (according to Soviet regulations, this issue is regulated differently). In the regulations on the conclusion of work contracts, the obligations of the general contractor are defined in the most general terms, but the new Polish construction law of 1961 establishes in detail the obligations of the construction manager. The author believes that statutory obligations apply at least to the same extent to the general contractor. Due to the fact that the general contractor is entrusted with managerial, organizational and coordinating functions, it is necessary to distinguish the responsibility of the enterprise as a direct contractor and its responsibility for violation of the general contractor obligations. Finally, the author comes to a conclusion that a general contractor agreement should be considered as a special type of agreement which is only associated with a direct contractor agreement. This is a contracting agreement one of the elements of which is a promise that a third party, i.e. a subcontractor, will make the corresponding deliveries. At the same time, the contract between the general contractor and the subcontractor can be considered as pactum in favorem tertii. Ultimately, the general contractor agreement includes a guarantee obligation of the general contractor for subcontractors. / The author, however, points out that the direct responsibility of subcontractors to the investor does not contribute to improving the sense of responsibility for the performance of the general contractor functions. Problems of preliminary contracts in construction. Due to the insufficient development of the construction industry in relation to the existing needs in capital construction, there are special bodies in Poland which deal with balancing investment tasks with the production capacities of the construction enterprises, setting priorities and distributing work between individual enterprises. Therefore, the socialized contractors cannot accept orders at their own discretion, since they must be accepted by special commissions for the distribution of work. / The author deals with the civil law consequences of such an order acceptance procedure. According to the regulations governing the construction contracts (agreements), the mere acceptance of order entails only the consequences of a preliminary contract (pactum de contrahendo).According to the provisions of the Polish Code of Obligations, a preliminary contract guarantees the creditor only a claim for damages in the event of non-fulfilment of the direct contract (agreement). The author believes that, under the existing procedure for the administrative distribution of work, the order acceptance by the commission for the distribution of work should be equivalent to the conclusion of a preliminary contract (agreement) giving the right to claim the conclusion of a direct contract (agreement). In the structure of the preliminary contract, we can see the provisions of the Czechoslovak and East German laws on business contracts to which the author refers. Structure of a direct construction contract (agreement). Due to the wide variety of subjects, construction contracts cannot be as strictly regulated as, for example, supply contracts. The special resolutions regulating them are of a more general nature, and the parties have an obligation to establish precisely the subject matter of the contract which is especially important for social and economic reasons, because the costs of useless construction represent an inevitable loss. Considering the procedure for concluding contracts established by law, the author points out that the Polish law does not provide for the mandatory participation of subcontractors in the drafting of the contract by the general contractor which cannot be considered correct. According to the provisions of the current law, the condition for concluding a contract (agreement) is that the investor has: 1) an approved project and estimate, 2) legal documentation establishing the localization and confirming the right of the investor to own the construction site, 3) providing financial resources to pay for the ordered work. Considering these obligations, the author notes that particular difficulties arise in connection with design and estimate documentation a significant part of which is usually delivered already in the course of work. The contractors are usually not liable for the project defects, but to some extent they have the obligation to check the documents. In the author’s opinion, the contractor should bear the legal consequences of the losses caused due to the defects in the documentation, since these defects can be discovered by showing ordinary diligence. The obligation to submit legal documentation is combined with the obligation to place the construction site at the disposal of the contractor. We mean not only the land plot itself but also the powers that would allow proper development of the construction site, and they may include the right to enter the adjacent, someone else’s plot. Then we consider the issues of supply of materials, machines and equipment, machine installation, acceptance of the facility and remuneration of the contractor. Arguing from the point of view of the law the publication of which is desirable, the author states that only a few of the special provisions of the Code of Obligations regulating the contracting agreement are directly applicable to the construction and installation agreements in the socialist economy; most of them have been modified in special regulations. This dictates the need for the future Civil Code to regulate planned construction contracts (agreements) separately from the universal type of the contracting agreement.